Suppose you are a solving a quadratic equation using the quadratic formula and this is your work so far:


2x2+7x−15=0

x=
−7 ±72−42−15
22​

x=
−7 ±???
4​👈

What number goes in place of ???

3 answers

To solve the quadratic equation \(2x^2 + 7x - 15 = 0\) using the quadratic formula, we first identify the coefficients:

  • \(a = 2\)
  • \(b = 7\)
  • \(c = -15\)

The quadratic formula is given by:

\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]

Now, we need to calculate the discriminant, \(b^2 - 4ac\):

  1. Calculate \(b^2\): \[ b^2 = 7^2 = 49 \]

  2. Calculate \(4ac\): \[ 4ac = 4 \cdot 2 \cdot (-15) = 8 \cdot (-15) = -120 \]

  3. Now calculate the discriminant \(b^2 - 4ac\): \[ b^2 - 4ac = 49 - (-120) = 49 + 120 = 169 \]

Now, we substitute this back into the quadratic formula:

\[ x = \frac{-7 \pm \sqrt{169}}{4} \]

The square root of 169 is 13. Thus, we can replace ??? with 13, so it would look like this:

\[ x = \frac{-7 \pm 13}{4} \]

Therefore, the value that goes in place of ??? is 13.

are you sure

Yes, I'm confident in the calculation, but let's confirm the steps to ensure everything is clear.

Given the quadratic equation:

\[ 2x^2 + 7x - 15 = 0 \]

We identify the coefficients:

  • \(a = 2\)
  • \(b = 7\)
  • \(c = -15\)

Now we apply the quadratic formula, which is:

\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]

Step 1: Calculate \(b^2 - 4ac\)

  1. Calculate \(b^2\): \[ b^2 = 7^2 = 49 \]

  2. Calculate \(4ac\): \[ 4ac = 4 \cdot 2 \cdot (-15) = 8 \cdot (-15) = -120 \]

  3. Calculate the discriminant: \[ b^2 - 4ac = 49 - (-120) = 49 + 120 = 169 \]

Step 2: Substitute into the formula

Now we substitute the values back into the quadratic formula:

\[ x = \frac{-7 \pm \sqrt{169}}{2 \times 2} \]

The square root of 169 is 13:

\[ x = \frac{-7 \pm 13}{4} \]

Thus, the number that goes in place of ??? is indeed 13.

Let me know if you have any further questions!